2018
DOI: 10.1590/1982-021620182019016
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular dysfunction and postural balance in cochlear implant users: a narrative literature review

Abstract: Cochlear implants directly stimulate nerve fibers and ganglion cells of the auditory nerve, which transform sound energy into low levels of electrical current, stimulating the remaining fibers of the auditory nerve in patients with severe to profound hearing loss, in order to provide the significant range of auditory sensation and speech comprehension. Due to the close relationship between cochlea and vestibular receptors, some patients may present vestibular and postural balance changes concomitantly after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…3 Greater occurrence of vestibular alteration in patients with bilateral CI may be because those with unilateral implantation are more able to compensate for the vestibular alteration at the injured side. 7 Vestibular dysfunction has more often been recorded among adult post-lingual cochlear implantees, especially in profound deafness due to long standing Meniere's syndrome and cochlear otosclerosis. After cochlear implantation in very young pre-lingual children lesser than 5 years of age, clinical signs of vertigo like nystagmus are most often not seen and these children are not able to provide a history of vertiginous symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Greater occurrence of vestibular alteration in patients with bilateral CI may be because those with unilateral implantation are more able to compensate for the vestibular alteration at the injured side. 7 Vestibular dysfunction has more often been recorded among adult post-lingual cochlear implantees, especially in profound deafness due to long standing Meniere's syndrome and cochlear otosclerosis. After cochlear implantation in very young pre-lingual children lesser than 5 years of age, clinical signs of vertigo like nystagmus are most often not seen and these children are not able to provide a history of vertiginous symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…5 Preservation of the residual hearing and vestibular function should be attempted using minimally invasive surgical techniques. 7 Karimi et al reported that in 6 of 9 patients, resealing of the cochleostomy improved vertigo. 10 Nguyen et al described techniques of atraumatic implant insertion thereby conserving residual inner ear function.…”
Section: Discussionmentioning
confidence: 99%